Stability of a model Fe-14Cr nanostructured ferritic alloy after long-term thermal creep. (September 2019) - Massey, Caleb P.; Hoelzer, David T.; Edmondson, Philip D.; Kini, Anoop; Gault, Baptiste; Terrani, Kurt A.; Zinkle, Steven J.
Abstract: The successful development of advanced materials such as nanostructured ferritic alloys (NFA) for next generation nuclear reactor concepts and ultra-supercritical steam power plants requires information on long term thermal creep. To support this initiative, this work examines the NFA MA957 (Fe-14Cr-1.0Ti-0.3Mo + 0.3Y2 O3 in wt%) crept to 61, 251 h at 825 °C and 70 MPa, the longest creep test available to date for this material. Using atom probe tomography and electron microscopy, it is shown that the grain size and nanoprecipitate size/composition are unaffected following this 7 yr creep test, although significant porosity is noted throughout the microstructure attributed to microvoid coalescence and growth. Graphical abstract: Unlabelled Image